Correlates of blood pressure according to early, on time, and late maturation in adolescents - Werneck, André O.; Silva, Danilo R. P.; Souza, Mariana F.; Christofaro, Diego G. D. [UNESP]; Tomeleri, Crisieli M.; Fernandes, Rômulo A. [UNESP]; Ronque, Enio R. V.; Coelho-e-Silva, Manuel J.; Sardinha, Luís B.; Cyrino, Edilson S. (Wiley-Blackwell, 2015)
The aim of this study was to estimate the prevalence and correlates of blood pressure (BP) according to somatic maturation in Southern Brazilian adolescents. A total of 1321 adolescents participated in the study (732 girls), aged between 10 and 16 years, enrolled in public schools. The assessment of BP was performed using oscillometric equipment. Measurements of body weight, height, waist circumference, and skinfold thickness were performed. Somatic maturation was estimated by the age at peak height velocity. Behavioral and hereditary variables were obtained using a questionnaire. Early-maturing adolescents had the highest prevalence of high BP (28%; 95% confidence interval, 24.6-33.5) compared with other maturational groups (P=.003). In late-maturing adolescents, the variables associated with BP were paternal hypertension (systolic BP: β=4.9; diastolic BP: β=5.3) and early physical activity (systolic BP: β=-4.0; diastolic DBP: β=-3.6). In average-maturing adolescents, waist circumference (systolic BP: β=0.3), body mass index (diastolic BP: β=0.5), and mother's hypertension (diastolic BP: β=1.8) were positively related to BP. In early-maturing adolescents, only waist circumference (systolic BP: β=0.3; diastolic BP: β=0.3) was associated with BP. The authors conclude that the prevalence of high BP is greater in adolescents with early maturity and the outcome appears to be related to biological indicators in this group. On the other hand, in late-maturing adolescents, behavioral and hereditary variables are more related to BP.